2002
DOI: 10.1210/jcem.87.1.8133
|View full text |Cite
|
Sign up to set email alerts
|

GNAS1Lesions in Pseudohypoparathyroidism Ia and Ic: Genotype Phenotype Relationship and Evidence of the Maternal Transmission of the Hormonal Resistance

Abstract: We conducted clinical and biological studies including screening for mutations in the gene encoding the alpha subunit of G(s) (GNAS1) in 30 subjects (21 unrelated families) with Albright's hereditary osteodystrophy (AHO), pseudohypoparathyroidism (PHP); and decreased erythrocyte G(s) activity (PHP-Ia; n = 19); AHO and decreased erythrocyte G(s) activity (isolated AHO; n = 10); or AHO, hormonal resistance, and normal erythrocyte G(s) activity (PHP-Ic; n = 1). A heterozygous GNAS1 gene lesion was found in 14 of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 107 publications
(17 citation statements)
references
References 41 publications
1
16
0
Order By: Relevance
“…Sussane Thiele et al described 5 patients diagnosed as PHP-Ic in whom they found TSH and PTH resistance, with normal Gsα activity and inherited maternal inactivating mutations in GNAS exons [21]. Linglart et al [22] in a study on genotype, phenotype relationship on the maternal transmission of the hormonal resistance did not observe any relationship between the erythrocyte Gsα activity and the phenotype which may justify our findings in this patient.…”
Section: Discussionsupporting
confidence: 46%
“…Sussane Thiele et al described 5 patients diagnosed as PHP-Ic in whom they found TSH and PTH resistance, with normal Gsα activity and inherited maternal inactivating mutations in GNAS exons [21]. Linglart et al [22] in a study on genotype, phenotype relationship on the maternal transmission of the hormonal resistance did not observe any relationship between the erythrocyte Gsα activity and the phenotype which may justify our findings in this patient.…”
Section: Discussionsupporting
confidence: 46%
“…Calcitonin resistance has been described without clinical features in patients affected with PHP1A (27). Elevated follicular-stimulating hormone (FSH) and luteinizing hormone (LH) levels were reported both by us and Namnoum et al (78,100). Glucagon and adrenaline resistances were demonstrated in patients Figure 3 Patterns of brachydactyly type E associated with iPPSD.…”
Section: Other Hormone Resistancesmentioning
confidence: 92%
“…Different molecular defects have been identified in patients with PHP1C, i.e. LOI at GNAS and four lossof-function mutations in the GNAS carboxyl-terminus leading to a conserved adenylyl cyclase receptorindependent activation but disrupted receptormediated activation (29,30,78).…”
Section: Challenges and Limitations Of The Current Classificationmentioning
confidence: 99%
“…Consistent with this imprinted mode of inheritance of hormone resistance, Gs␣ expression occurs predominantly from the maternal allele in certain human tissues, including the thyroid gland (9)(10)(11), the ovary (9), and the pituitary gland (12). In the renal cortex, there is evidence for both biallelic (13) and maternal expression of Gs␣ (14). AHO, unlike hormone resistance, develops after both paternal and maternal transmission of Gs␣ mutations.…”
mentioning
confidence: 86%